2022
DOI: 10.3390/healthcare10101955
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships between Physical Activity, Screen Time and Sleep Time According to the Adolescents’ Sex and the Day of the Week

Abstract: This study had two aims: (1) to identify the levels of physical activity, screen time and sleep time of adolescents according to the sex of the participant and the day of the week; (2) to find out the relationships between physical activity, screen time and sleep time according to the sex of the participant and the day of the week. The study design was non-experimental, descriptive-correlational and cross-sectional. The sample consisted of 694 adolescents in Compulsory Secondary Education from Soria (Spain). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This might be due to the times our data were collected. We used morning and evening, which are usually considered the busy hours for park use, as supported by Sanz-Martín et al [73], who suggested that weekend evenings were the most suitable times for MVPA. Moreover, compared to other groups of visitors, older adults have different perspectives, requirements, and preferences when using urban parks, as stated in one Romanian study [74].…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the times our data were collected. We used morning and evening, which are usually considered the busy hours for park use, as supported by Sanz-Martín et al [73], who suggested that weekend evenings were the most suitable times for MVPA. Moreover, compared to other groups of visitors, older adults have different perspectives, requirements, and preferences when using urban parks, as stated in one Romanian study [74].…”
Section: Discussionmentioning
confidence: 99%
“…6 Seluruh pertanyaan yang terkait dengan pengetahuan disusun dengan menggunakan jawaban pilihan berganda dengan acuan jawaban benar merefleksikan Pedoman Gizi Seimbang dan Pedoman dalam melakukan aktivitas fisik yang dianjurkan serta waktu menatap layar yang disarankan (screen time guideline). 19,20 Seperti halnya pada pengetahuan dan sikap gizi, pertanyaan pada kuesioner praktik makan juga terbukti valid dan reliabel. Pertanyaan yang teruji valid dan reliabel dari kuesioner ini telah mewakili unsur-unsur dalam diet sehat berkelanjutan.…”
Section: Pembahasanunclassified
“…For instance, Sanz-Martín et al highlight the growing prevalence of sedentary lifestyles among young people and the potential long-term health consequences [20]. Sanz-Martin et al also emphasise the public health implications of this inactivity, particularly concerning occupational health and performance [21]. Furthermore, González-Valero et al provide insights into how early lifestyle choices can impact physical and psychological well-being in high-stress careers like law enforcement [22].…”
Section: Introductionmentioning
confidence: 99%